Al2O3 triggered in-situ crystallization of Gd3Al2Ga3O12 in glass and enhancement in magnetic and Faraday rotating properties. Issue 8 (July 2023) - Wang, Shun; Chen, Qiuling
Abstract: Nanocrystals doped transparent glasses or glass ceramics have shown promising tunable magnetic and magneto-optical performance. In this study, the Al2 O3 -induced in-situ crystallization of Gd3 Al2 Ga3 O12 in tellurite glass was reported. 10–20 nm-cubic Gd3 Al2 Ga3 O12 ( Ia3d space group) nanocrystals formed in tellurite glass with Al2 O3 content ≤ 0.75 mol% by 400 °C-heat treatment. When Al2 O3 content in glass was higher than 0.75 mol%, excessive Al2 O3 triggered the crystallization of orthorhombic GdAlO3 ( Pnma ) in which the Gd and Al ions existed as octahedral GdO8 and AlO6 units at a temperature higher than 398 °C. The in-situ crystallization influenced the glass network structure, broke the linkage of tetrahedral TeO4, and BO4, and formed trigonal pyramids TeO3 and BO3 instead. At the same time, nuclear magnetic resonance spectra revealed the conversion of AlO4 → AlO6, GaO4 → GaO6, and the changes from bridging oxygen to non-bridging oxygen as well. From energy-dispersive X-Ray analysis, Gd 3+ clusters were observed, leading to the ferromagnetism of glass. Electron paramagnetic resonance spectra witnessed an enhancement of the Zeeman effect which is the reason for the improvement of Faraday rotation. Tellurite glass with 0.75 mol% Al2 O3 after 400 °C-annealing (A75) showed a giant Verdet constant of 93 rad/T.m at 633 nm which is superior to most of the values from the literature.